Factors Affecting the Financial Performance of Cooperative Businesses in Palembang City - Ummi Kalsum; Arradytia Permana; Randy Hidayat; Patricia Ayu Dewayanti (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
Not all cooperatives in Palembang City are able to show good financial performance, even though they operate in a similar environment. The difference in the acquisition of Residual Business Results (SHU) is one of the indicators of factors that affect the success of cooperatives. This study analyses the influence of the number of members, own Capital, loan capital, and business volume on cooperatives’ remaining business results (SHU) in Palembang City. The focus of the analysis includes the impact of each of these variables on the SHU of primary cooperatives that are active and registered with the Palembang City Cooperatives and SMEs Office. This study uses a purposive sampling method with a sample of 56 cooperatives. The data were analyzed using panel data regression to explore the relationship and influence of independent variables on dependent variables. The study results show that the number of members, own Capital, and business volume significantly influence the increase in cooperative SHU. Capital has made the most significant contribution to SHU, while the volume of business and the number of members also have a considerable impact. However, the loan capital was found to have no significant influence on the cooperative SHU. These findings highlight the importance of internal capital management and strategies to increase business volume to optimize the financial performance of cooperatives in Palembang City. To increase SHU, cooperatives are encouraged to actively socialize the benefits of being a cooperative member to the public.; implementing a transparent accounting system and financial reports can increase members’ confidence in using their own capital and loan capital, as well as provide training to cooperative administrators regarding financial management, marketing, and business operations.